Utilization and Management of Forest Resources: under the Ambit of JFM-a Case Study of Ausgram Forest Beat of Burdwan District in West Bengal - Batabyal, Siuli; Parvhn, Mobina; Tah, Jagatpati; Banerjee, Ratan (Indian Forester, 2011)
The present study was undertaken by the workers with the help of Divisional Forest Office in its Ausgram Beat area under Guskara Range alongwith the members of Forest Protection Committee. It was emphasized for the socio-economic upliftment of the rural people in its adjoining areas. Three classes of people viz. very poor, poor and middle class were considered in this context for including their livelihood status in this survey report .